Method for rapidly testing construction workability of polyurethane mixture

By measuring the isocyanate group content with an infrared spectrometer and conducting uniaxial penetration strength tests, a multiple linear regression model was established to solve the problems of low accuracy and long cycle in the construction and workability judgment of polyurethane mixtures, achieving fast and accurate construction and workability judgment, and improving road quality.

CN120820403APending Publication Date: 2025-10-21SHANXI JIBEI HIGHWAY MAINTENANCE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510812525.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

The existing technology has low accuracy in construction and workability judgment of polyurethane mixtures, and the laboratory testing method has a long cycle, which makes it difficult to meet the requirements of quickly opening traffic on the construction site.

Method used

The isocyanate group content in the polyurethane adhesive was measured using an infrared spectrometer. Combined with the uniaxial penetration strength test, a multiple linear regression model was established to quickly determine the construction workability.

Benefits of technology

It enables rapid and accurate judgment of the construction and workability of polyurethane mixtures at the construction site, reduces the influence of subjective judgment of technicians, and improves the quality and service life of road paving.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005456262650000101
    Figure BDA0005456262650000101
  • Figure BDA0005456262650000111
    Figure BDA0005456262650000111
  • Figure BDA0005456262650000121
    Figure BDA0005456262650000121
Patent Text Reader

Abstract

The invention provides a method for rapidly testing the construction workability of a polyurethane mixture. The method comprises the following steps: maintaining each part of polyurethane mixture sample for different time, respectively taking part of the polyurethane mixture sample to extract the polyurethane adhesive, carrying out infrared spectroscopic analysis on each part of the polyurethane adhesive to obtain the infrared characteristic peak area of an isocyanate group, and calculating the content of the polyurethane adhesive based on the infrared characteristic peak area. Calculating to obtain percentage contents of isocyanate groups corresponding to different curing times; testing the void ratio, the Marshall stability and the penetration strength of each polyurethane mixture sample to obtain the void ratios, the Marshall stability and the penetration strength corresponding to different curing times; by taking the percentage content of the isocyanate group as a first independent variable and the penetration strength as a second independent variable, respectively carrying out multiple linear regression fitting on the porosity and the Marshall stability; and finally obtaining the void ratio and Marshall stability of the to-be-detected polyurethane mixture, thereby obtaining the construction workability of the to-be-detected polyurethane mixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for quickly testing the construction workability of a polyurethane mixture, and belongs to the field of road engineering detection. Background Art

[0002] Polyurethane mixture is a new type of road paving material with advantages such as high modulus, strong high-temperature resistance, strong Marshall stability, high splitting strength, and rutting resistance. It can solve pavement problems such as cracks, looseness, rutting, surface oil depletion, aging, and reduced skid resistance, significantly extending the service life of the pavement.

[0003] The construction workability of polyurethane mixture refers to the fact that the newly mixed polyurethane mixture is easy to operate in each construction process (mixing, transportation, pouring, tamping, etc.) and can obtain uniform quality and dense molding. Better construction workability helps to form a denser structure, obtain better porosity and better road performance.

[0004] Polyurethane mixtures use a polyurethane adhesive instead of asphalt to bond the stone aggregates. Polyurethane adhesives are polymer adhesives formed by the chemical reaction of polyisocyanates and polyols, resulting in a repeating urethane structure in the molecular chain. Unreacted polyurethane is generally a pale yellow, viscous liquid. Unlike traditional asphalt mixtures, which gain strength simply by lowering the temperature, polyurethane mixtures develop their strength through the reaction between the polyurethane adhesive and water. This water can come from additional water applied during the paving process or from moisture in the air. The curing process of polyurethane is irreversible once it reacts with water. Therefore, after the polyurethane mixture is mixed in the factory and loaded onto the site, it will continue to react with moisture in the air, often being partially reacted by the time it arrives.

[0005] Partial reaction of the polyurethane mixture can severely affect paving and rolling performance, resulting in difficulties with compaction, actual void ratios far exceeding the target, low strength, cracks, and other issues, all of which affect road performance. Therefore, it is crucial to determine whether the polyurethane mixture delivered to the site meets paving conditions and determine the construction holding time.

[0006] Unlike asphalt mixtures, the reaction rate of the polyurethane adhesive within polyurethane mixtures is dependent on both temperature and humidity, making it difficult to establish a unified standard. Currently, workability is primarily determined by on-site construction technicians through visual inspection based on their experience, which results in significant errors and limited reliability. While simple and quick, the visual method relies heavily on the experience of on-site construction technicians, observing conditions such as the gloss and wetness of the aggregate. This leads to issues such as a lack of quantification and low accuracy. Even for technicians who have extensive experience in polyurethane field construction, the accuracy of their on-site judgments is only 80%. Problems such as cracks and uneven compaction that have occurred in test sections currently paved using visual judgment by construction technicians are all caused by errors in this visual method.

[0007] Currently, there are some laboratory testing methods to determine workability, such as forming Marshall specimens to test void content and Marshall stability. The specific experimental steps are as follows: 1. Place coarse aggregate and fine aggregate in a 105°C oven for at least 3 hours. Then, adjust the oven temperature to 30°C and allow to cool to 30°C before use. The residual moisture content of coarse aggregate and fine aggregate after drying and cooling should not be higher than 0.1%; 2. Take out the coarse and fine aggregate from the oven, weigh the coarse and fine aggregate and polyurethane adhesive according to the designed mix ratio at 30℃ and mix for 90s, then add the mineral powder and mix for 90s; 3. Use the compaction method to form the Marshall specimen; 4. Place the specimen together with the test mold on its side in an environment with a temperature of 25℃ and a humidity of 70%RH±5%RH for curing for 24h±1h, and then place it in an environment with a temperature of 50℃±3℃ and a humidity of 80%RH±5%RH for curing for 72h±1h; 5. Take out the specimen and place it on its side on the ground, cool it at room temperature for at least 12h and then demould it; 6. Perform Marshall stability and porosity tests on the demoulded specimen to judge the construction and workability of the polyurethane mixture accordingly. Although this method can determine the construction and workability of polyurethane mixtures, laboratory molding often takes 5 days, and subsequent testing and data processing are required, which often takes a week or even longer. It is difficult to meet the requirements of short construction period and rapid opening of traffic at the construction site, and has serious lags.

[0008] Therefore, developing a method for quickly testing the construction and workability of polyurethane mixtures has become a technical problem that needs to be solved urgently. Summary of the Invention

[0009] Problems to be solved by the invention

[0010] In response to technical issues existing in the prior art, such as the low accuracy of visual inspection methods and the long testing cycles of laboratory methods, the present invention first provides a method for rapidly testing the workability of polyurethane mixtures. This method utilizes an infrared spectrometer to measure and calibrate the percentage of isocyanate groups within the polyurethane adhesive, thereby determining the degree of reactivity. Furthermore, combined with indoor uniaxial penetration strength tests, the relationship between the percentage of isocyanate groups and on-site workability is determined, establishing a simple and rapid method for determining on-site workability and retention time.

[0011] Solutions for solving problems

[0012] The present invention provides a method for quickly testing the construction workability of a polyurethane mixture, which comprises the following steps:

[0013] Obtain multiple identical polyurethane mixture samples, take portions of each polyurethane mixture sample after curing for different periods of time, extract polyurethane adhesive, perform infrared spectroscopy analysis on each polyurethane adhesive, obtain the infrared characteristic peak area of ​​the isocyanate group in each polyurethane adhesive, and calculate the percentage of isocyanate groups corresponding to different curing times based on the infrared characteristic peak area;

[0014] Part of each polyurethane mixture sample was taken to prepare a Marshall specimen, and the void ratio and Marshall stability were tested to obtain the void ratio and Marshall stability corresponding to different curing times;

[0015] Take some polyurethane mixture samples from each polyurethane mixture to conduct penetration strength test to obtain the penetration strength corresponding to different curing times;

[0016] Taking the percentage of isocyanate groups as the first independent variable and the penetration strength as the second independent variable, multiple linear regression fitting was performed on the porosity and Marshall stability respectively to obtain two sets of multiple linear regression fitting relationships;

[0017] Based on two sets of multiple linear regression fitting relationships, the void ratio and Marshall stability of the polyurethane mixture to be tested are obtained, and based on the void ratio and Marshall stability of the polyurethane mixture to be tested, the construction workability of the polyurethane mixture to be tested is obtained.

[0018] According to the method for rapidly testing the workability of a polyurethane mixture of the present invention, the workability of the polyurethane mixture to be tested is judged by the following method:

[0019] If the porosity of the polyurethane mixture to be tested is less than or equal to 8% and the Marshall stability is greater than or equal to 50 MPa, the construction and workability of the polyurethane mixture to be tested meets the requirements.

[0020] According to the method for quickly testing the construction workability of polyurethane mixtures of the present invention, if the void ratio of the polyurethane mixture to be tested is greater than 8%, and / or the Marshall stability of the polyurethane mixture to be tested is less than 50 MPa, the pavement of the polyurethane mixture to be tested does not meet the construction workability requirements.

[0021] According to the method for rapidly testing the construction and workability of a polyurethane mixture of the present invention, an infrared spectrum analysis is performed on each portion of the polyurethane adhesive using an Agilent Technologies Cary630 FTIR infrared spectrometer to obtain the infrared characteristic peak area of ​​the polyurethane adhesive in each portion of the polyurethane mixture sample.

[0022] According to the method for rapidly testing the construction and workability of a polyurethane mixture of the present invention, there is a relationship between the infrared characteristic peak area of ​​the isocyanate group in each portion of the polyurethane adhesive and the percentage of the isocyanate group as shown in the following formula (1):

[0023] Infrared characteristic peak area = 3.8347X 异氰酸酯基团百分含量 -15.552 (1).

[0024] According to the method for rapidly testing the workability of a polyurethane mixture of the present invention, assuming that the porosity of the polyurethane mixture sample is y1, the percentage of isocyanate groups in the polyurethane adhesive is x1, and the penetration strength of the polyurethane mixture sample is x2, there exists a multiple linear regression fitting relationship as shown in the following formula (2):

[0025] y1=0.38x1+5.20x2+1.29 (2).

[0026] According to the method for rapidly testing the workability of a polyurethane mixture according to the present invention, assuming that the Marshall stability of the polyurethane mixture sample is y2, the percentage of isocyanate groups in the polyurethane adhesive is x1, and the penetration strength of the polyurethane mixture sample is x2, there exists a multiple linear regression fitting relationship as shown in the following formula (3):

[0027] y2=-1.74x1-28.95x2+112.06 (3).

[0028] According to the method for quickly testing the construction and workability of polyurethane mixtures of the present invention, the polyurethane mixture sample comprises polyurethane and graded aggregate; preferably, the rubber-aggregate ratio of the polyurethane mixture sample is 1-10%, preferably 4-7%.

[0029] According to the method for quickly testing the construction and workability of a polyurethane mixture of the present invention, the polyurethane comprises one or a combination of two or more of 6170 polyurethane adhesive, 6191 polyurethane adhesive, 6192 polyurethane adhesive or 5-2 polyurethane adhesive;

[0030] According to the method for quickly testing the construction workability of polyurethane mixtures of the present invention, the graded aggregate includes one of AC-13 gradation, AC-16 gradation, AC-20 gradation or AC-25 gradation.

[0031] Effects of the Invention

[0032] The present invention can facilitate on-site testing with an infrared spectrometer at the construction site, can quickly output results, and guide on-site construction personnel on whether the vehicle mixture meets the construction and workability requirements. At the same time, combined with the uniaxial penetration strength indoor test, the variability of on-site infrared spectrum testing can be reduced, greatly reducing the impact of subjective judgment by technicians, thereby improving the pavement paving level and pavement service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A photo showing the Agilent Technologies Cary630 FTIR infrared spectrometer in use;

[0034] Figure 2 Shows the apparatus for the uniaxial penetration test and photos of the penetration test;

[0035] Figure 3 The multiple linear regression fitting process of the void ratio y1, the percentage of isocyanate groups x1 and the penetration strength x2 is shown;

[0036] Figure 4 The multiple linear regression fitting process of Marshall stability y2, percentage of isocyanate groups x1 and penetration strength x2 is shown. DETAILED DESCRIPTION

[0037] Various exemplary embodiments, features, and aspects of the present invention will be described in detail below. The word "exemplary" is used herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as superior or preferred over other embodiments.

[0038] In addition, numerous specific details are provided in the following detailed description to better illustrate the present invention. Those skilled in the art will appreciate that the present invention can be practiced without certain specific details. In other instances, methods, means, equipment, and steps well known to those skilled in the art are not described in detail in order to highlight the main points of the present invention.

[0039] Unless otherwise stated, the units used in this specification are international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0040] In this specification, the use of "may" includes both the meaning of performing a certain process and the meaning of not performing a certain process.

[0041] In this specification, references to "some specific / preferred embodiments," "other specific / preferred embodiments," "embodiments," etc., mean that the specific elements (e.g., features, structures, properties, and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not be present in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0042] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints A and B.

[0043] In this specification, "multiple linear regression" is also called "multi-factor linear regression", which studies the quantitative dependence between a dependent variable and multiple independent variables, wherein the multiple independent variables include two or more independent variables.

[0044] The present invention provides a method for quickly testing the construction workability of a polyurethane mixture, which comprises the following steps:

[0045] Obtain multiple identical polyurethane mixture samples, take portions of each polyurethane mixture sample after curing for different periods of time, extract polyurethane adhesive, perform infrared spectroscopy analysis on each polyurethane adhesive, obtain the infrared characteristic peak area of ​​the isocyanate group in each polyurethane adhesive, and calculate the percentage of isocyanate groups corresponding to different curing times based on the infrared characteristic peak area;

[0046] Part of each polyurethane mixture sample was taken to prepare a Marshall specimen, and the void ratio and Marshall stability were tested to obtain the void ratio and Marshall stability corresponding to different curing times;

[0047] Take some polyurethane mixture samples from each polyurethane mixture to conduct penetration strength test to obtain the penetration strength corresponding to different curing times;

[0048] Taking the percentage of isocyanate groups as the first independent variable and the penetration strength as the second independent variable, multiple linear regression fitting was performed on the porosity and Marshall stability respectively to obtain two sets of multiple linear regression fitting relationships;

[0049] Based on two sets of multiple linear regression fitting relationships, the void ratio and Marshall stability of the polyurethane mixture to be tested are obtained, and based on the void ratio and Marshall stability of the polyurethane mixture to be tested, the construction workability of the polyurethane mixture to be tested is obtained.

[0050] In the present invention, current construction specifications often use the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTGE20-2011, T0702-2011 Compaction Method) to form Marshall specimens of polyurethane mixtures, and judge whether the polyurethane mixture to be tested meets the on-site construction compaction standards based on the stability and void ratio of the Marshall specimens. Specifically, the workability of the polyurethane mixture to be tested is judged as follows: if the void ratio of the polyurethane mixture to be tested is less than or equal to 8% and the Marshall stability is greater than or equal to 50 MPa, then the workability of the polyurethane mixture to be tested meets the requirements. Furthermore, if the void ratio of the polyurethane mixture to be tested is greater than 8% and / or the Marshall stability is less than 50 MPa, then the pavement of the polyurethane mixture to be tested does not meet the workability requirements.

[0051] In the present invention, there is no particular limitation on the number of identical polyurethane mixture samples, which can generally be 5-50 parts, for example, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, etc.

[0052] In the present invention, the curing method is not particularly limited, as long as multiple polyurethane mixture samples are cured under the same conditions. Specifically, the curing temperature can be 15-35°C, and the curing humidity can be 40-90%. During the curing process, the temperature and humidity must be maintained constant.

[0053] In the present invention, the method for extracting the polyurethane adhesive is not particularly limited. Generally, the polyurethane adhesive is obtained by centrifugal extraction according to Method T0617 of the "Testing Procedures for Asphalt and Asphalt Mixtures in Highway Engineering." In the present invention, when extracting the polyurethane adhesive from a polyurethane mixture sample, the polyurethane mixture sample can comprise 1 / 6 to 1 / 4 of each polyurethane mixture sample.

[0054] In some specific embodiments, such as Figure 1 As shown, infrared spectroscopy analysis of the polyurethane adhesive was performed using an Agilent Technologies Cary 630 FTIR spectrometer to determine the infrared peak area of ​​the isocyanate groups in each polyurethane adhesive. The portable Agilent Technologies Cary 630 FTIR spectrometer can be used for on-site testing at the construction site, providing results in approximately ten minutes.

[0055] Specifically, use a pipette to drop about 0.2-5 μL of polyurethane adhesive onto the diamond crystal of Agilent Technologies' Cary 630 FTIR infrared spectrometer, ensuring that the droplet completely covers the crystal. To reduce the consumption of isocyanate groups by water vapor in the air, the test is performed quickly after the droplet is completed.

[0056] In some specific embodiments, the infrared characteristic peak area of ​​the isocyanate group in each polyurethane adhesive and the percentage of the isocyanate group are related as shown in the following formula (1):

[0057] Infrared characteristic peak area = 3.8347X 异氰酸酯基团含量 -15.552 (1).

[0058] For formula (1), the method of the prior art can be used as needed, for example, using an infrared spectrometer to obtain the infrared characteristic peak area of ​​the isocyanate group in the polyurethane adhesive, then testing the polyurethane adhesive by potentiometric titration to obtain the percentage of the isocyanate group in the polyurethane adhesive, and then using linear fitting to obtain the relationship between the infrared characteristic peak area of ​​the isocyanate group in the polyurethane adhesive and the percentage of the isocyanate group. Of course, the present invention can also be directly obtained based on literature records, such as the literature "Quantitative Determination of Isocyanate Group Content in Polyurethane Prepolymers Using ATR-FTIR".

[0059] In the present invention, void content can be tested according to the "Testing Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011, T0708-2011 Volumetric Method), and Marshall stability can be tested according to the "Testing Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011, T0709-2011). Specific testing methods can be conducted in accordance with these procedures and will not be detailed here. Furthermore, when testing void content and Marshall stability, the polyurethane mixture sample used can comprise 1 / 5 to 3 / 5 of each polyurethane mixture sample.

[0060] Further, if Figure 2 As shown, penetration strength tests can be conducted in accordance with Appendix F of the "Highway Asphalt Pavement Design Specification" (JTGD50-2017). A metal striker is driven into the test piece using a hydraulic press, and the point of maximum force is the penetration strength of the test piece. Specific testing methods can be performed according to the "Regulations" and will not be detailed here. Furthermore, when conducting penetration strength tests, the polyurethane mixture sample used can comprise 1 / 5-3 / 5 of each polyurethane mixture sample.

[0061] In the present invention, the percentage of isocyanate groups is used as the first independent variable, the penetration strength is used as the second independent variable, and multiple linear regression fitting is performed on the porosity and Marshall stability to obtain two sets of multiple linear regression fitting relationships.

[0062] Specifically, assuming that the porosity of the polyurethane mixture sample is y1, the percentage of isocyanate groups in the polyurethane adhesive is x1, and the penetration strength of the polyurethane mixture sample is x2, there is a multiple linear regression fitting relationship as shown in the following formula (2):

[0063] y1=0.38x1+5.20x2+1.29 (2)

[0064] Specifically, assuming that the Marshall stability of the polyurethane mixture sample is y2, the percentage of isocyanate groups in the polyurethane adhesive is x1, and the penetration strength of the polyurethane mixture sample is x2, there is a multiple linear regression fitting relationship as shown in the following formula (3):

[0065] y2=-1.74x1-28.95x2+112.06 (3)

[0066] In some specific embodiments, the polyurethane mixture sample comprises polyurethane and graded aggregate; preferably, the polyurethane mixture sample has a rubber-to-aggregate ratio of 1-10%, preferably 4-7%. In the present invention, the rubber-to-aggregate ratio refers to the ratio of polyurethane to graded aggregate in the polyurethane mixture sample.

[0067] In some specific embodiments, the polyurethane includes one or a combination of two or more of 6170 polyurethane adhesive, 6191 polyurethane adhesive, 6192 polyurethane adhesive or 5-2 polyurethane adhesive; the graded aggregate includes one of AC-13 gradation, AC-16 gradation, AC-20 gradation or AC-25 gradation.

[0068] In the present invention, the polyurethane mixture to be tested is substantially the same as the polyurethane mixture sample used in the curve fitting, that is, the polyurethane and graded aggregate in the polyurethane mixture sample are substantially the same as those in the polyurethane mixture to be tested, and the ratio of rubber to aggregate is also substantially the same.

[0069] This invention proposes a rapid and accurate method for determining the workability of polyurethane mixtures. By utilizing the continuous consumption of isocyanate groups during the reaction of polyurethane adhesives, the isocyanate group content within the polyurethane mixture can be rapidly determined using FTIR infrared spectroscopy. Furthermore, to address the issue of large errors in single variables, the invention incorporates and integrates indoor penetration strength testing to establish a relationship between isocyanate content, penetration strength, and on-site workability. This provides a reliable, rapid, and economical method for determining the on-site workability of polyurethane mixtures.

[0070] Example

[0071] The embodiments of the present invention will be described in detail below with reference to the examples, but it will be understood by those skilled in the art that the following examples are merely illustrative of the present invention and should not be construed as limiting the scope of the invention. Where specific conditions are not specified in the examples, the methods were performed according to conventional conditions or the conditions recommended by the manufacturer. Where the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be obtained commercially.

[0072] Preparation of fitting curve:

[0073] 1) Ten groups of freshly mixed polyurethane mixtures with a 6% adhesive-to-bitumen ratio, each weighing 5000 g, were cured in a standard temperature and humidity room at 25°C and 70% humidity for 30 min, 60 min, 90 min, 120 min, 150 min, 180 min, 210 min, 240 min, 270 min, and 300 min, respectively. Then, 1000 g of the polyurethane mixture from each group was centrifuged and extracted using method T0617 of the "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" to obtain a polyurethane adhesive.

[0074] The polyurethane used in the polyurethane mixture is 6170 polyurethane adhesive. The gradation of the aggregate of the polyurethane mixture adopts AC-13 gradation, as shown in Table 1 below:

[0075] Table 1

[0076]

[0077] 2. Using Agilent Technologies Cary630 FTIR infrared spectrometer ( Figure 1 ), infrared spectroscopy analysis was performed on each group of extracted polyurethane adhesives. For infrared spectroscopy analysis, a pipette was used to drop about 1.5 μL of the polyurethane adhesive sample onto the diamond crystal of the FTIR infrared spectrometer to ensure that the droplet completely covered the crystal. In order to reduce the consumption of isocyanate groups by water vapor in the air, a quick scan was performed after the droplet was completed.

[0078] 3. Since the infrared characteristic peak area of ​​the isocyanate group in the polyurethane adhesive and the percentage of the isocyanate group are related as shown in the following formula (1), the percentage of the isocyanate group in the polyurethane adhesive can be determined according to the formula (1):

[0079] Infrared characteristic peak area = 3.8347X 异氰酸酯基团的百分含量 -15.552 (1)

[0080] The percentage of isocyanate groups corresponding to different curing times can be calculated using the above formula (1), and the results are shown in Table 2 below.

[0081] Table 2

[0082] Curing time (min) Percentage of isocyanate groups (%) 30 11.86 60 10.76 90 9.83 120 8.98 150 7.86 180 7.13 210 6.01 240 5.14 270 4.23 300 3.21

[0083] 4. After extracting the polyurethane adhesive, a 2000 g sample was taken from each portion of the polyurethane mixture remaining. Marshall specimens were formed according to the specified gradation. The void content was tested according to the "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011, T0708-2011 Volumetric Method) and the Marshall stability was tested according to the "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011, T0709-2011). The results are shown in Table 3.

[0084] 5. After extracting the polyurethane adhesive, a 2000g sample was taken from each remaining polyurethane mixture. According to the penetration strength test in Appendix F of the Highway Asphalt Pavement Design Specification (JTG D50-2017), a metal striker was inserted into the test piece using a hydraulic press. The point where the force was maximized was the penetration strength of the test piece. The results are shown in Table 3.

[0085] Table 3

[0086]

[0087] 6. Using the percentage of isocyanate groups as the first independent variable x1 and the penetration strength as the second independent variable x2, multiple linear regression fitting is performed on the porosity y1 and the Marshall stability y2, respectively. Figure 3 and Figure 4 The fitting results are shown in Table 4 below.

[0088] Table 4

[0089]

[0090] As shown in Table 4, the multiple linear regression fitting correlation coefficient R 2 The multiple linear regression fitting correlation coefficient of Marshall stability is 0.912, R 2 The fitting accuracy is 0.905, which is relatively high.

[0091] According to the above multiple linear regression fitting results, the polyurethane mixtures of the following examples were subjected to relevant tests, and the standards are: if the void ratio of the polyurethane mixture is less than or equal to 8% and the Marshall stability is greater than or equal to 50 MPa, it indicates that the pavement using the polyurethane mixture meets the construction and workability requirements; if the void ratio of the polyurethane mixture is greater than 8%, and / or the Marshall stability is less than 50 MPa, it indicates that the pavement using the polyurethane mixture does not meet the performance requirements.

[0092] Example 1

[0093] A 3000g sample of the first commercially purchased polyurethane mixture, freshly mixed at the factory, was taken as the polyurethane mixture to be tested. After the required time for transportation from the mixing plant to the site (one hour in this example), 2000g of the polyurethane mixture to be tested was taken to the laboratory for a penetration strength test. The test result was 0.27 kN. The first commercially purchased polyurethane mixture was essentially the same as the polyurethane mixture used in the curve fitting.

[0094] 2. Take 1000g of the polyurethane mixture to be tested and extract it according to the above method to obtain the polyurethane adhesive. Figure 1 ), the polyurethane adhesive in the polyurethane mixture was subjected to infrared spectroscopy analysis. In the infrared spectroscopy analysis, about 1.5 μL of the polyurethane adhesive extracted from the surface of the polyurethane mixture was dropped onto the diamond crystal of the FTIR infrared spectrometer using a pipette to ensure that the droplet completely covered the crystal. In order to reduce the consumption of isocyanate groups by water vapor in the air, the test was performed quickly after the droplet was completed, and the peak area was 14.742.

[0095] 3. Since the infrared characteristic peak area of ​​the isocyanate group in the polyurethane adhesive and the percentage of the isocyanate group are related as shown in the following formula (1), the percentage of the isocyanate group in the polyurethane adhesive can be determined to be approximately 7.9% based on the formula (1), that is, X is approximately 7.9.

[0096] Infrared characteristic peak area = 3.8347X 异氰酸酯基团百分含量 -15.552 (1)

[0097] 4. Based on the multiple linear regression curves in Table 3, the void ratio and Marshall stability were approximately 5.70% and 90.50 MPa, respectively. Since the void ratio was <8% and the Marshall stability was >50 MPa, the pavement was considered to meet performance requirements. Visual inspection by on-site construction personnel revealed a uniform, glossy, moist surface with no noticeable lumps. Therefore, the pavement was considered suitable for paving and released for unloading and paving.

[0098] Example 2

[0099] A 3000g sample of the second commercially available polyurethane mixture, freshly mixed at the factory, was taken as the polyurethane mixture to be tested. After the required time for transportation from the mixing plant to the site (4 hours in this example), 2000g of the polyurethane mixture to be tested was taken to the laboratory for penetration strength testing. The test result was 0.91 kN. The second commercially available polyurethane mixture was essentially the same as the polyurethane mixture used in the curve fitting.

[0100] 2. Take 1000g of the polyurethane mixture to be tested and extract it according to the above method to obtain the polyurethane adhesive. Figure 1 ), the extracted polyurethane adhesive was subjected to infrared spectroscopy analysis. In the infrared spectroscopy analysis, about 1.5 μL of the extracted polyurethane adhesive was dropped onto the diamond crystal of the FTIR infrared spectrometer using a pipette to ensure that the droplet completely covered the crystal. In order to reduce the consumption of isocyanate groups by water vapor in the air, the test was performed quickly after the droplet was completed, and the peak area was 5.155.

[0101] 3. Since the infrared characteristic peak area of ​​the isocyanate group in the polyurethane adhesive and the percentage of the isocyanate group are related as shown in the following formula (1), the percentage of the isocyanate group in the polyurethane adhesive can be determined to be approximately 5.4% based on the formula (1), that is, X is approximately 5.4.

[0102] Infrared characteristic peak area = 3.8347X 异氰酸酯基团百分含量 -15.552 (1)

[0103] 4. Based on the multiple linear regression curves in Table 3, the void fraction and Marshall stability were calculated to be 8.07% and 76.35 MPa, respectively. This example passed the test with a Marshall stability greater than 50 MPa. However, due to a void fraction greater than 8%, it was deemed unsuitable for paving. Furthermore, visual inspection by on-site construction personnel revealed that the mixture was dry and exhibited significant clumping, thus defining it as waste. Construction was prohibited with this vehicle's mixture.

[0104] It should be noted that, although the technical solutions of the present invention are described with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0105] While various embodiments of the present invention have been described above, the above descriptions are intended to be illustrative, non-exhaustive, and not limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is selected to best explain the principles of the embodiments, their practical applications, or technological improvements in the marketplace, or to enable others skilled in the art to understand the embodiments disclosed herein.

Claims

1. A method for quickly testing the construction workability of polyurethane mixtures, characterized in that: The following steps are involved: Obtain multiple identical polyurethane mixture samples, take portions of each polyurethane mixture sample after curing for different periods of time, extract polyurethane adhesive, perform infrared spectroscopy analysis on each polyurethane adhesive, obtain the infrared characteristic peak area of ​​the isocyanate group in each polyurethane adhesive, and calculate the percentage of isocyanate groups corresponding to different curing times based on the infrared characteristic peak area; Part of each polyurethane mixture sample was taken to prepare a Marshall specimen, and the void ratio and Marshall stability were tested to obtain the void ratio and Marshall stability corresponding to different curing times; Take some polyurethane mixture samples from each polyurethane mixture to conduct penetration strength test to obtain the penetration strength corresponding to different curing times; Taking the percentage of isocyanate groups as the first independent variable and the penetration strength as the second independent variable, multiple linear regression fitting was performed on the porosity and Marshall stability respectively to obtain two sets of multiple linear regression fitting relationships; Based on two sets of multiple linear regression fitting relationships, the void ratio and Marshall stability of the polyurethane mixture to be tested are obtained, and based on the void ratio and Marshall stability of the polyurethane mixture to be tested, the construction workability of the polyurethane mixture to be tested is obtained.

2. The method for quickly testing the construction workability of polyurethane mixture according to claim 1, wherein: The workability of the polyurethane mixture to be tested is judged by the following method: If the porosity of the polyurethane mixture to be tested is less than or equal to 8% and the Marshall stability is greater than or equal to 50 MPa, the construction and workability of the polyurethane mixture to be tested meets the requirements.

3. The method for quickly testing the construction workability of polyurethane mixture according to claim 1 or 2, characterized in that, If the void ratio of the polyurethane mixture to be tested is greater than 8%, and / or the Marshall stability of the polyurethane mixture to be tested is less than 50 MPa, the pavement of the polyurethane mixture to be tested does not meet the construction and workability requirements.

4. The method for quickly testing the construction workability of a polyurethane mixture according to any one of claims 1 to 3, characterized in that: The infrared spectrum of each polyurethane adhesive was analyzed using an Agilent Technologies Cary630 FTIR infrared spectrometer to obtain the infrared characteristic peak area of ​​the isocyanate group in each polyurethane adhesive.

5. The method for quickly testing the construction workability of a polyurethane mixture according to any one of claims 1 to 4, characterized in that: The relationship between the infrared characteristic peak area of ​​the isocyanate group in each polyurethane adhesive and the percentage of the isocyanate group is as shown in the following formula (1): Infrared characteristic peak area = 3.8347X 异氰酸酯基团百分含量 -15.552 (1).

6. The method for quickly testing the construction workability of a polyurethane mixture according to any one of claims 1 to 5, characterized in that: Assuming that the void ratio of the polyurethane mixture sample is y1, the percentage of isocyanate groups in the polyurethane adhesive is x1, and the penetration strength of the polyurethane mixture sample is x2, there is a multiple linear regression fitting relationship as shown in the following formula (2): y1=0.44x1+5.91x2+0.36 (2).

7. The method for quickly testing the construction workability of a polyurethane mixture according to any one of claims 1 to 6, characterized in that: Assuming the Marshall stability of the polyurethane mixture sample is y2, the percentage of isocyanate groups in the polyurethane adhesive is x1, and the penetration strength of the polyurethane mixture sample is x2, there is a multiple linear regression fitting relationship as shown in the following formula (3): y2=-1.74x1-28.95x2+112.06 (3).

8. The method for quickly testing the construction workability of a polyurethane mixture according to any one of claims 1 to 7, characterized in that: The polyurethane mixture sample comprises polyurethane and graded aggregate; preferably, the rubber-aggregate ratio of the polyurethane mixture sample is 1-10%, preferably 4-7%.

9. The method for quickly testing the construction workability of polyurethane mixture according to claim 8, characterized in that: The polyurethane includes one or a combination of two or more of 6170 polyurethane adhesive, 6191 polyurethane adhesive, 6192 polyurethane adhesive or 5-2 polyurethane adhesive.

10. The method for quickly testing the construction workability of a polyurethane mixture according to claim 8 or 9, wherein: The graded aggregate includes one of AC-13 gradation, AC-16 gradation, AC-20 gradation or AC-25 gradation.